The Consequence of the Siege of Temeşvar: Analysis and Evaluation of the Submission Letter of the Castellan Mustafa Pasha (1716) - Bekir Gökpınar (Türkiyat Mecmuası)
During the reign of Süleiman the Magnificent, the Ottoman conquests were directed toward the west. The conquest of central Hungary by the Ottomans in particular was the beginning of a long struggle. It was both difficult and costly for the Ottomans to hold the region and a significant part of the region, which remained under Ottoman rule for about 150 years, was lost in the "Holy League" wars. With the Treaty of Karlowitz, the last piece of land to the north of the Danube in Hungary was the province of Temeşvar. As the province of Temeşvar was by that time a frontier region, Ottomans made some military,financial and administrative arrangements there in order to keep Temeşvar because they predicted that this place would one day be the target of Austria. Indeed, after Damad Ali Pasha’s defeat in Varadin in 1716, the Austrian forces chose the Temeşvar castle as their first target and Prince Eugene besieged the castle with a large army. The Ottoman military administration could not send sufficient military aid here due to the recent defeat. The castle commander, Mustafa Pasha, continued his resistance for 57 days with a small number of soldiers. But the castle was handed over to the Austrian forces when no help came as a result of the long defense. After the castle was surrendered, Mustafa Pasha came to Belgrade and sent a letter to the sultan about the defense and delivery process of the castle. This paper, in the submission letter (arz) of the Castellan of Temesvar, Mustafa Pasha, attempts to analyze the siege of the castle by the Habsburg forces, the defense of the fortress, the situation of the people of the castle, the military aid that did not come despite the distress call, the surrender process and the issues that emerged afterward. The information in the Pasha’s submission letter has been evaluated based on other sources belonging to the period.